Consistency Analysis of Precipitation Characteristics of Mu Us Sandy Land Based on Daily Precipitation Data - MA Lan; LIU Dengfeng; BAI Bing; REN Mengzhi; HUANG Qiang; LIN Mu (Renmin Zhujiang)
Mu Us Sandy Land is located in Yulin city of Shaanxi province and Ordos city of Inner Mongolia Autonomous Region,where the ecological and hydrological system is relatively fragile.However,precipitation is an important controlling factor to the evolution of the ecology and hydrology.Meanwhile,the intensity and process of precipitation also have a crucial influence on ecosystem.Therefore,it is necessary to evaluate the consistency of precipitation characteristic value sequences in Mu Us Sandy Land.Based on daily precipitation data from 1957 to 2019 at 10 meteorological stations in Mu Us Sand Land,this paper selects four precipitation characteristic value sequences namely annual precipitation,annual maximum daily precipitation,annual longest continuous precipitation and annual longest continuous precipitation days,and analyzes the trend by Mann-Kendall method,the abrupt change by sliding t test,and the period by continuous wavelet analysis for evaluating the consistency of precipitation characteristic value sequences.The results indicate that:On the whole,the precipitation characteristic value sequences show a decreasing trend;The significant abrupt change points occur in 1970—1990 and after 2000;The main period of the precipitation characteristic value is about 35 years.